Islamic Religious Education Learning Management in the Merdeka Curriculum at Asa Cendekia Junior High School - Silvana Izza Rahma Dewi; Istikomah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
Islamic Religious Education (PAI) learning management in the Merdeka Belajar Curriculum emphasizes flexibility and creativity in teaching. This curriculum is designed to improve the quality of education, educators must be given the opportunity to develop more innovative and responsive learning methods that suit the needs of students. In this context, PAI learning in the Merdeka Curriculum focuses more on strengthening character education. Therefore, educators are expected to use learning management proportionally through the steps of planning, organizing, implementing, and evaluating. This study examines the learning management of Islamic Religious Education in the Merdeka Curriculum at Asa Cendekia Junior High School. This research was conducted using a qualitative method through data collection using interviews, observation, and documentation involving the principal and Islamic Religious Education (PAI) subject teachers. The results showed that the implementation of Islamic Religious Education learning management at Asa Cendekia Junior High School is well structured and integrated. This has a positive impact, not only on academic achievement, but also on the character building of students as noble individuals.